Research on Automatic Recovery Strategy for Metro Train Delay - QING Guangming; LI Jianghong; ZHANG Zhaoyang; ZHANG Yu (Kongzhi Yu Xinxi Jishu)
Aiming at the problems of train delay caused by factors such as passenger flow fluctuations, operational failures, etc., an automatic recovery method for metro train delay was established suitable for full-length and short-turn routing based on train operating organization strategy. Combined with the constraints such as train safety operation and service demand, a mathematical model and a solution method for the adjustment and optimization of the delayed operation of the train were established. Correctness of the delay recovery strategy and algorithm are verified by CRS-Track, a train operation simulation software.